Antipyretic Activity Assessment Of Justicia Adhatoda L. Whole Plant Extract - Alok Kumar Dash (Revista Electronica de Veterinaria, 2024)
Objective: In the present investigation was Anti-pyretic activity Assessment of Justicia adhatoda L.  Whole part of methanol extract (JAWME) against Brewer's yeast suspension induces   rats.Methods: To produce fever, a 20% (w/v) suspension of brewer's yeast (10 ml/kg) was administered subcutaneously into the animal's back area. The temperature in the rectum of each participant was measured using a thermometer 17 hours after the injection. The experiments were carried out just on rats that showed a temperature rise of at least 0.7°C. The test samples were given orally after a duration of 17 hours, and the temperature was monitored at 1, 2, 3, 4, 5, and 6 hours after the administration of the medicine. Each group employed six rodents . The dose of Normal control (DW)         5 ml/kg, Brewer's yeast suspension           10ml/kg,Standard (Aspirin)150 mg/kg,Extract JAV    200 mg/kg and Isolated compound ICFJ    40 mg/kgResult: Phytochemical screening result revealed the presence of saponins, flavonoids, alkaloids, etc. The stipulated plant Justicia adhatoda L.  Whole part of methanol extract (JAWME) possess significance antipyretic property as comparable to standard drug AspirinConclusion: The methanolic extract of Justicia adhatoda L reveals the reduction in the body temperature level as compare to Standard drug (Aspirin). The result suggests that Justicia adhatoda L possesses anti-pyretic property.